The role of lymphocyte-C-reactive protein ratio in the prognosis of gastrointestinal cancer: a systematic review and meta-analysis - Liu, XiaoMeng; Zhang, JingChen; An, HaoYu; Wang, WanYao; Zheng, YuKun; Wei, FengJiang (Frontiers in Oncology, 2024)
Objective The lymphocyte-to-C-reactive protein (LCR) ratio, an immune-inflammatory marker, shows prognostic potential in various cancers. However, its utility in gastrointestinal malignancies remains uncertain due to inconsistent findings. This systematic review and meta-analysis synthesizes recent evidence to elucidate the association between LCR and prognosis in gastrointestinal cancer patients, aiming to clarify LCR’s potential role as a prognostic biomarker. Methods We searched PubMed, Embase, Cochrane, and Web of Science databases up to May 2024 to evaluate the association between LCR and prognosis in gastrointestinal cancer patients. The main outcomes included overall survival (OS), recurrence-free survival (RFS), and disease-free survival (DFS). We also analyzed secondary parameters such as geographical region, study duration, sample size, LCR threshold, and patient characteristics (age, gender, tumor location, and TNM stage). Results This meta-analysis of 21 cohort studies (n=9,131) finds a significant association between reduced LCR levels and poor prognosis in gastrointestinal cancer. Lower LCR levels were associated with worse overall survival (HR=2.01, 95% CI=1.75-2.31, P<0.001), recurrence-free survival (HR=1.90, 95% CI=1.32-2.76, P<0.001), and disease-free survival (HR=1.76, 95% CI=1.45-2.13, P<0.001). Subgroup analyses by cancer type, timing, and LCR threshold consistently confirmed this relationship (P<0.05). Conclusion LCR may serve as a prognostic marker in gastrointestinal cancer patients, with lower LCR levels associated with poorer prognosis. However, more high-quality studies are needed to validate these findings, considering the limitations of the current evidence. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier CRD42023486858.